ANALISIS TIME SERIES TERHADAP INDEKS HARGA KONSUMEN (IHK) KABUPATEN CILACAP DENGAN AUTOREGRESSIVE INTEGRATED MOVING AVERAGE DALAM PERSPEKTIF ISLAM - Laili, Ummiy Fauziyah (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2012)
The economy is one of the cornerstone of life. Economic indicators can be seen from the consumer price index which shows the rate of increase or decrease the price by year basis. The increase of prices causes inflation of the area. One of the areas in Indonesia who receives the impact of rising prices or inflation is Cilacap district. Cilacap is the largest district in Central Java that economic development would have a major impact on the economy of Central Java Province. The levels of the economy Cilacap district can be seen from the consumer price index (CPI), the higher the Consumer Price Index (CPI) will lead to increasing inflation. CPI is an index that describes the development of prices of goods and services occurs. This research has been done on the CPI forecast for some future period using the Autoregressive Integrated Moving Average (ARIMA). Data CPI in January 2009 to June 2011 are used as training data for modeling purposes and obtained the following results: Zt = 0.205744 + 1.5996) + 0.4822 Zt Zt-1-2-1.0818-3 Zt While data on the CPI from July to December 2011 is used as the testing data and the data is obtained by the model error rate 0.0893988%. Based on ARIMA model equations have been obtained, it can be used to predict the value of the Consumer Price Index (CPI) in January 2012 for 128.4362, 128.9642 by February, the month of March 2012 at 129.4865, April 2012 at 130.0053, May 2012 at 130.5222, June 2012 at 131.0378, July 2012 at 131.5527, August 2012 at 132.0672, September 2012 at 132.5814 and 133.0954 of the month in October 2012. The results of the consumer price index forecasting for the coming months look up every month, the increasing prices are possible because of mismatch between demand and supplies due to imperfect competition in the market. According to public opinion, the higher prices to be paid because people do a monopoly significantly to reduce the income of employees and the poor in general, and this is inconsistent with the spirit of the Qur'an and Sunnah, because it is not sociable and depriving the poor people also society completely.